Arthrodesis of the Distal Interphalangeal Joint in a Horse Using Stainless Steel Baskets and Transarticular 4.5-mm Cortical Screws - Honnas, C. M.; Vacek, J. R.; Schumacher, J. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
The distal interphalangeal joint was successfully arthrodesed in a 7-monthold horse using two 13-mm stainless steel baskets that were packed with autogenous cancellous bone and held in place with transarticular 4.5-mm cortical screws. The baskets were placed midway between the extensor process of the distal phalanx and the collateral ligament on the corresponding side of the joint. The screws were directed from the abaxial side of the middle phalanx, axially and distally through the basket and across the joint space, into the distal phalanx. Bony fusion of the distal interphalangeal joint occurred through the region occupied by the baskets as well as through the central region of the joint. The horse was free of lameness at the walk in the operated limb from the fourth until the tenth postoperative month, at which time lameness recurred as a result of sepsis in the region of the lateral implant. An additional complication was the development of a carpus varus deformity in the contralateral forelimb, presumably as a result of stretching of the lateral collateral carpal ligaments from excessive weight-bearing coupled with an abnormal posture (tripod stance) during convalescence. The horse was euthanatized 10 months after the arthodesis procedure because of severe lameness associated with sepsis in the region of the lateral implant.Arthrodesis of the distal interphalangeal joint can be accomplished by inserting perforated stainless steel baskets into the joint.Modifications in the surgical approach to avoid complications of sepsis need to be made before this technique can be recommended for clinical application.Although the horse did not survive long-term, presentation of this technique should prove useful to other investigators as they attempt to devise techniques to fuse the distal interphalangeal joint.
Keywords: Equine; distal interphalangeal joint; arthrodesis